(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This study investigates how digital tools and artificial intelligence (AI) can enhance listening and speaking instruction for 17 upper-intermediate university students. The approach combines authentic audio, communicative speaking tasks, and AI-based pronunciation and feedback tools. Results show clear improvement in listening comprehension, fluency, pronunciation, and learner confidence. The study concludes that well-integrated digital and AI-supported methods effectively strengthen oral communication skills in modern EFL classrooms.